2023
DOI: 10.1088/1402-4896/acdcc8
|View full text |Cite
|
Sign up to set email alerts
|

Realizing efficient THz circular dichroism using ultra-thin chiral metasurface

Abstract: Circular dichroism is characterized by distinct optical responses for left-handed and right-handed circularly polarized waves widely used for biological monitoring, analytical chemistry, and plasmonic sensing. In this work, we propose a chiral metasurface composed of a Mushroom-shaped (MS) pattern to achieve circular dichroism in reflection mode at THz frequencies. The maximum achieved absorption efficiency is 98.49% for left-handed circularly polarized (LCP) incident wave while for right-handed circularly pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Table 1 shows a comparison of the proposed CMA with some recently reported ones. Compared with previous works, 30,32,35,38,41–43 our proposed CMA introduces a temperature-tunable material InSb, which can dynamically adjust the CD effect, and has the advantage of a simple structure. Therefore, the proposed CMA shows superior properties in the material selection, structural design, tunable bandwidth, etc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows a comparison of the proposed CMA with some recently reported ones. Compared with previous works, 30,32,35,38,41–43 our proposed CMA introduces a temperature-tunable material InSb, which can dynamically adjust the CD effect, and has the advantage of a simple structure. Therefore, the proposed CMA shows superior properties in the material selection, structural design, tunable bandwidth, etc.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, CMAs that operate at microwave, terahertz (THz), and even visible frequencies have garnered significant attention because of their chiral-selective absorption with strong CD effects that are significantly greater than those observed in natural materials. 19–34 For instance, Tang et al theoretically and experimentally demonstrated a CMA with η-shaped resonators that exhibited a maximum absorption of over 80% with a CD value of approximately 0.5 in the visible frequencies. 23 Wang et al proposed a dual-band CMA using distorted ‘I’ shaped resonators, which exhibited a maximum absorbance of 95.18% and 91.77% at 12.04 GHz and 14.22 GHz for the LCP waves, respectively, and a maximum CD value of 0.6 at 12.5 GHz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 6 G communication near 0.3 THz have been recently reported. Modulating the polarization of the incident wave front has been extensively studied in different regimes of the electromagnetic spectrum [16][17][18][19]. High efficiency and wide bandwidth are the main goals of the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral metasurfaces, which are the two-dimensional counterparts of chiral metamaterials, have received significant interest from researchers due to their potential for reduced cost and simplified fabrication processes. Compared with conventional metasurfaces, chiral metasurfaces have tremendous features, such as a negative refractive index [10], conversion of polarization [11][12][13][14][15][16][17][18][19][20][21], asymmetric transmission (AT) [22][23][24][25][26][27][28][29][30][31][32][33][34], and circular dichroism (CD) [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%